2020
DOI: 10.1051/0004-6361/201936667
|View full text |Cite
|
Sign up to set email alerts
|

Wave amplitude modulation in fan loops as observed by AIA/SDO

Abstract: Aims. We perform a detailed analysis to understand the evolution and dynamics of propagating intensity disturbances observed in a fan loop system. Methods. We performed multiwavelength time-distance analysis of a fan loop system anchored in an isolated sunspot region (AR 12553). The active region was observed by the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory. We measured the phase speeds of the propagating intensity disturbances by employing cross-correlation analysis, and by obtainin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…These results compelled the authors to conclude that the coronal slow waves are externally driven by the global solar oscillations (p-modes) in the photosphere. A recent study by Sharma et al (2020) also show similar amplitude modulation in slow waves observed in a sunspot across different layers of the solar atmosphere possibly confirming the wider applicability of this interpretation. Utilising high-resolution multi-wavelength observations of a sunspot from 16 different channels, Zhao et al (2016) studied the propagation of slow waves from photosphere to corona.…”
Section: Active Regionssupporting
confidence: 74%
“…These results compelled the authors to conclude that the coronal slow waves are externally driven by the global solar oscillations (p-modes) in the photosphere. A recent study by Sharma et al (2020) also show similar amplitude modulation in slow waves observed in a sunspot across different layers of the solar atmosphere possibly confirming the wider applicability of this interpretation. Utilising high-resolution multi-wavelength observations of a sunspot from 16 different channels, Zhao et al (2016) studied the propagation of slow waves from photosphere to corona.…”
Section: Active Regionssupporting
confidence: 74%
“…These results compelled the authors to conclude that the coronal slow waves are externally driven by the global solar oscillations (p-modes) in the photosphere. A recent study by Sharma et al (2020) also shows similar amplitude modulation in slow waves observed in a sunspot across different layers of the solar atmosphere possibly confirming the wider applicability of this interpretation. Utilising high-resolution multi-wavelength observations of a sunspot from 16 different channels, Zhao et al (2016) studied the propagation of slow waves from photosphere to corona.…”
Section: Active Regionssupporting
confidence: 73%
“…There are also a couple of studies reporting a temperature-dependent PD velocity (Krishna Prasad, Banerjee, and Singh, 2012; Uritsky et al, 2013), which is a characteristic of slow-mode magneto-acoustic waves. However, several other studies did not reveal any obvious temperature dependence (Tian et al, 2011b;Sharma et al, 2020). A statistical study by Kiddie et al (2012) showed that the temperature dependency appears to be clear only for PDs rooted in sunspots.…”
Section: Waves or Flowsmentioning
confidence: 92%